INOVASI TEKNOLOGI PANGAN (INTIP) PADA PETANI TRANSMIGRASI DALAM UPAYA MEWUJUDKAN RICE ESTATE DAN KEMANDIRIAN PANGAN DI DUSUN PERINDUNG DAN ANGSIANA, KABUPATEN KUBU RAYA - Edy Suryadi; Eko Sarwono (Jurnal Buletin Al-Ribaath, 2017)
Perindung and Angsiana village are majorly inhabited by transmigrants with livelihood as rice farmers. Yields of up to 10 tons each year. This is great potential to be developed towards real rice and food self-sufficiency. There are two issues on rice farming in both villages, which are the drying process depends on the sunlight and the use of threshing machines that need fuel. Community service was done in the form of training and making the simple drying machine utilizing biomass such as rice husk as a source of biomass. In addition to the manufacture of paddy drying machine, we also trained local farmer to create a simple threshing machine. The results of these activities were increasing knowledge of local farmer through training and socialization. They included the manufacture of a threshing machine, rice dryer machine, and cassava flour processing machine. We hope the local government will be the motivator and the facilitator for the community to increase community empowerment and increase the potential for rural areas and communities can develop and apply the knowledge they have been given during the community service. Keywords : Farmer, rice, Pal Sembilan Village, Kubu Raya Regency